2012
DOI: 10.1029/2011gl050765
|View full text |Cite
|
Sign up to set email alerts
|

The effect of translation speed upon the intensity of tropical cyclones over the tropical ocean

Abstract: During the past several decades operational forecasts of tropical cyclone (TC) tracks have improved steadily, but intensity forecast skills have experienced rather modest improvements. Here we use 40 years of TC track data to show that storm intensity correlates with translation speed, with hurricanes of category 5 moving on average 1 m s−1 faster than tropical storms. This correlation provides evidence that the translation speed of a storm can exert a significant control on the intensity of storms by modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 28 publications
(39 reference statements)
14
122
0
Order By: Relevance
“…Table 1 shows slowly moving storms (F r < 1) are fewer in category-4 and À5 (18%) than in weaker storms (23 and 28%). Therefore, our data here roughly agrees with the result of Mei et al [2012].…”
Section: Discussionsupporting
confidence: 92%
“…Table 1 shows slowly moving storms (F r < 1) are fewer in category-4 and À5 (18%) than in weaker storms (23 and 28%). Therefore, our data here roughly agrees with the result of Mei et al [2012].…”
Section: Discussionsupporting
confidence: 92%
“…The mean of translation speed is calculated for each bin of wind speed. Mei et al (2012) found a net increase of U h with TC category from global TC data. In this study, the mean U h also correlates closely with the maximum sustained wind speed (The correlation coefficient R = 0.96 in the NH and R = 0.94 in the SH).…”
Section: Methodsmentioning
confidence: 88%
“…Another aspect to note from the overall analysis is the relationship between the translational speed of the protohurricanes and their degree of intensification, an idea pointed out by Mei et al [38]. Although our simulations do not use the 1D model option for ocean mixed-layer representation and hence do not incorporate wind-induced SST cooling with its negative feedback to the storm, yet, intriguingly enough, our results show that the simulations creating the most intense proto-Tomas perturbations, the groups KF-KF and NGE-NGE, are also those that bring the system furthest from their origin and so create the fastest translational speeds.…”
Section: Intensity and Trajectory Analysismentioning
confidence: 99%